Model-Driven Development in Robotics Domain: A Systematic Literature Review - Heineck, Tiago; Gonçalves, Enyo; Sousa, Aêda; Oliveira, Marcos; Castro, Jaelson (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2016: Anais do X Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2016)
Robots are complex agents composed of various sensors and actuators that work together with software to meet specific requirements. The subset of robots that has the ability to interact among them and even with people, through gestures or speaking, is known as Social Robots. Model-Driven Development is a promising paradigm because it promotes the reuse of components and quick code generation with quality. ModelDriven Development has been widely used in the context of Robotics in order to reduce complexity, reduce development effort and reuse of software. Due to these facts, it becomes pertinent the development of a systematic literature review to compile these results. In this paper we investigate how MDD techniques have helped the field of Robotics, therefore a systematic literature review was conducted seeking to identify approaches and their main technical features, as well as the types of specific requirements, behavioral and social issues. We came to conclusion that the existing approaches provide many interesting capabilities, typically by using the component-based development paradigm seeking a higher level of software reuse and facilitating the implementation of systems.